Pengaruh Penambahan Limbah Kulit Udang Terhadap Kualitas Kompos Tandan Kosong Kelapa Sawit untuk Memperbaiki Sifat Tanah di Majene - Kurniati; Dwi Ahrisa Putri; Dwi Ratnasari; Astina (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
Oil palm empty fruit bunches are palm oil industry waste that has not been processed and utilized optimally. Utilizing palm oil industrial waste as compost material can reduce the negative impact of waste on the environment. Compost as a source of organic matter and nutrients that can improve properties and restore soil function, so that plant nutrients are complete. The addition of shrimp shell waste can improve the quality of oil palm empty fruit bunches compost, namely the availability of macro and micro nutrients in the compost. The purpose of this study was to analyze effect of composting empty palm oil bunches with the addition of shrimp shell waste on the soil in Majene. The results of the analysis of primary macronutrients such as pH, C-Organic, Nitrogen, Phosphorus, Potassium and C/N Ratio in the soil after the addition of composted oil palm empty fruit bunches and shrimp shell waste increased. Meanwhile, secondary macro nutrients such as Calcium, Magnesium, Sulfur and micro nutrients such as Aluminum, iron and Manganese did not increase after the addition of composted empty fruit bunches of oil palm and shrimp shell waste.